Analisis Strategi Pembinaan Atlet oleh Dinas Kebudayaan Pariwisata Pemuda dan Olahraga Kabupaten Pati - Imansari, Adhisti Tiara; Dwimawanti, Ida Hayu; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2015)
This study aimed to explore alternative strategies for coaching athletes in Pati regency. The research process begins with identifying and analyzing strategic value, internal and external environment as well as enabling factors and inhibitors. The next process is to establish strategic issues using SWOT analysis and formulate development strategies. This is a descriptive qualitative research. Researchers will describe the situation on the ground and propose a development strategy as a recommendation to the government. Data collection techniques used were interviews and documentation. Determination of informants also obtained by purposive sampling technique, such as interviews with the Head of Department, Head of Section, KONI, coaches and athletes involved. Strategy coaching athletes obtained from the SWOT analysis there are four, Utilizing conformity the vision and mission with fostering the current condition as a foundation in early coaching ages, promote the welfare of athletes by utilizing the commitment of stakeholders, Improving the quality and quantity of human resources by utilizing the methods of competition and a stable political conditions, and Improving the quality of sports facilities and infrastructure in accordance with the standards by working with a third party.